The investigation of phases and conductivity of lithium chromium oxide (LiCr02) / Muhammad Azillah Azman - Azman, Muhammad Azillah (2012)
Lithium Chromium Oxide, LiCrC>2 being prepared by several synthesizing method. The phases of each material are investigated via X-Ray diffraction method and it was found out that all the material had a single phase, and after it is verified its phases, the conductivity test is carried out. The main objective of this study is to determine which synthesized material has the highest rate of conductivity.